BIOLISTRIK RAMAH LINGKUNGAN DARI MIKROBA EKSOELEKTROGENS TANAH PUPUK ORGANIK PADA BERBAGAI PENAMBAHAN AIR - Regina Zahrani Marza; Irdawati; Putri Amelya Ningsih; Muhammad Nazif Zen; Silvi Tamara; Echy Dania Putri; Dinda Aulia Nabila; Intan Feby Nasty (Universitas Cokroaminoto Palopo, 2026)
The increasing demand for electricity has triggered the development of environmentally friendly alternative energy sources. One promising innovative technology is the Microbial Fuel Cell (MFC), which utilizes electroactive microorganisms such as exoelectrogens to generate electricity from organic materials. This research aims to analyze the impact of organic fertilizer soil and the addition of water on bi-electricity production in MFC systems. The experiment was conducted using organic fertilizer soil as a substrate, with parameters such as voltage and power density being measured regularly. The results show that exoelectrogenic microbes can significantly enhance electricity production, with specific treatments (P2 U1) providing the highest stability in electricity generation over 24 hours. The addition of water also positively impacted microbial activity and electron transfer. This study reinforces the potential of organic fertilizer soil-based MFCs as a sustainable and environmentally friendly renewable energy source.